Composite solid electrolytes based on lithium doped N-methyl-N-propylpiperidinium salt - Kyzlasova, Daria A.; Ulihin, Artem S.; Uvarov, Nikolai F. (Электрохимическая энергетика)
The effect of lithium perchlorate (LiClO4) on the transport and thermal properties of the ternary system consisting of N-methyl-N-propylpiperidinium perchlorate, highly dispersed γ-aluminum oxide (having the specific surface area of 200 m2 /g), and lithium perchlorate was investigated. It was shown that the obtained composites exhibited thermal stability up to at least 190°C. Using the impedance spectroscopy method, it was shown that the highest conductivity of solid electrolytes was ~10–5 S/cm at 40°C, x = 0.5, and 3·10–4 S/cm at x = 0.55 (T = 110°С).